2009
DOI: 10.1016/j.resuscitation.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a computational platform for the analysis of the physiologic mechanisms of a human experimental model of hemorrhage

Abstract: Computational models of integrative physiology may serve as a framework for understanding the complex adaptive responses essential for homeostasis in critical illness and resuscitation and may provide insights for design of diagnostics and therapeutics. In this study a computer model of human physiology was compared to results obtained from experiments using Lower Body Negative Pressure (LBNP) analog model of human hemorrhage. LBNP has been demonstrated to produce physiologic changes in humans consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Some of these systems use a combination of sensors or changes in HR variability to determine when a person is in the early stages of hemorrhagic shock. [23][24][25][26] The results of early studies are promising, but these systems are not widely available. Until they do become available, TVS will continue to be the main way that patients at risk for dying from hemorrhagic shock are identified.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these systems use a combination of sensors or changes in HR variability to determine when a person is in the early stages of hemorrhagic shock. [23][24][25][26] The results of early studies are promising, but these systems are not widely available. Until they do become available, TVS will continue to be the main way that patients at risk for dying from hemorrhagic shock are identified.…”
Section: Discussionmentioning
confidence: 99%
“…Lower body negative pressure (LBNP) has been extensively utilized as an experimental technique to induce physiologically significant central hypovolemia, and can be used to simulate preshock hemorrhage in humans (4,9,44,51). Two recent studies reported comparable hemodynamic responses to LBNP and blood loss up to 1,000 ml in humans (21,36) and 25% loss of total blood volume in baboons (17).…”
mentioning
confidence: 99%
“…6 Complex laboratory tests using specialized equipment have also been implicated for early identification of patients at a higher risk of death from hemorrhagic shock; however, such resources may not always be available in the field or the emergency department. 7 In addition, the applicability, reliability, and cost-effectiveness of these parameters to identify hemodynamic instability in geriatric trauma patients remain unclear. 8 Shock index (SI) is a simple ratio of HR over SBP, which can be easily calculated in the field.…”
mentioning
confidence: 99%